O papel do professor de Educação Física nas séries iniciais do Ensino Fundamental - Santos, Geovane Pinheiro dos (BRASIL, 2024)
This course completion work (TCC) aimed to investigate the role of the Physical Education teacher in the training of students in the early years of elementary school in public schools in Parintins, AM. Field research was carried out with a qualitative approach with nine Physical Education teachers who work in state and municipal schools. As a data collection instrument, a semi-structured interview with eleven open questions was used. The importance of the teacher and physical education as a mandatory subject in the school curriculum was identified, which contributes to the physical, motor and affective-social development of students, through practices and methods adopted in classes. It is concluded that this study contributes to expanding the understanding of the role of the Physical Education teacher in the training of students, promoting discussions about their reality, pointing out ways to improve the discipline in the early years of elementary school.